2021
DOI: 10.3389/fcell.2021.665919
|View full text |Cite
|
Sign up to set email alerts
|

Feedback-Driven Mechanisms Between Phosphorylated Caveolin-1 and Contractile Actin Assemblies Instruct Persistent Cell Migration

Abstract: The actin cytoskeleton and membrane-associated caveolae contribute to active processes, such as cell morphogenesis and motility. How these two systems interact and control directional cell migration is an outstanding question but remains understudied. Here we identified a negative feedback between contractile actin assemblies and phosphorylated caveolin-1 (CAV-1) in migrating cells. Cytoplasmic CAV-1 vesicles display actin-associated motilities by sliding along actin filaments or/and coupling to do retrograde … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 67 publications
(80 reference statements)
1
17
0
Order By: Relevance
“…Previous research revealed that phosphorylation of Cav-1 is associated with the formation and internalization of caveolae and is involved in lots of cellular functions ( Han et al, 2021 ). Tyrosine residue Y14 located at the NH2-terminus of Cav-1 protein, is the premier phosphorylation site ( Shi et al, 2021 ). We thus speculated that change of Cav-1 Y14 phosphorylation status might contribute to Fas/Fap-1/Cav-1 cascade-controlled cytokine secretion of MSCs.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research revealed that phosphorylation of Cav-1 is associated with the formation and internalization of caveolae and is involved in lots of cellular functions ( Han et al, 2021 ). Tyrosine residue Y14 located at the NH2-terminus of Cav-1 protein, is the premier phosphorylation site ( Shi et al, 2021 ). We thus speculated that change of Cav-1 Y14 phosphorylation status might contribute to Fas/Fap-1/Cav-1 cascade-controlled cytokine secretion of MSCs.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we explored the mechanism by which the NS1643-induced dephosphorylation of Cav-1 inhibits cancer cell migration. Although the phosphorylation of Cav-1 was shown to promote cell migration by facilitating actin remodeling, focal adhesion turnover, pseudopodial protrusions, and stress fiber formation [ 25 , 48 ], in a previous study, we showed that the activation of Kv11.1 significantly increases β-catenin levels at the junctional membrane in MCF-7 cells [ 9 ]. Here, we observed the same effect of NS1643 in triple negative MDA-MB-231 cells, which was absent in Cav-1 depleted cells.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylated Cav-1 reciprocally enhances RhoA activity and facilitates focal adhesion turnover, leading to enhanced tumor cell migration. Cytoplasmic Cav-1 was shown to be associated with contractile actin filaments [ 25 ]. These authors showed that cytoplasmic Cav-1-positive vesicles move along actin filaments, but once Cav-1 is dephosphorylated, the motility of these vesicles is decreased, due to reduced RhoA-myosin Ⅱ activity and increased Rac1-PAK1-Cofillin activation, resulting in the disorganization of contractile stress fibers and compromised directional movement.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed the intimate links between caveolae/CAV-1 and stress fibers ( Echarri and Del Pozo, 2015 ). Our previous work also found that CAV-1 knockout led to disordered stress fibers and prominent lamellipodia by regulating the active level of RhoA–myosin II and Rac1–PAK1–Cofilin ( Shi et al, 2021 ). Inhibition of stress fibers, but not Arp2/3-dependent branched actin filaments, diminished the phosphorylation of CAV-1 on site Tyr14 ( Shi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 86%
“…Our previous work also found that CAV-1 knockout led to disordered stress fibers and prominent lamellipodia by regulating the active level of RhoA–myosin II and Rac1–PAK1–Cofilin ( Shi et al, 2021 ). Inhibition of stress fibers, but not Arp2/3-dependent branched actin filaments, diminished the phosphorylation of CAV-1 on site Tyr14 ( Shi et al, 2021 ). It has been reported that CAV-1-regulated actin-related mechanosensitive pathways was closely related to its regulation on RhoA activity ( Peng et al, 2007 ).…”
Section: Introductionmentioning
confidence: 86%